La formación de maestros en Michoacán 1885 – 1949 - Piñón Bravo, Josué Arafat (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The training of teachers in the country has been configured as a long-term process that was influenced by the socio-historical context it went through, coming to reconfigure, mutate and transform to adapt to the political-social needs not only of the State but also of society as a whole. The axis of transformation revolved around the political intention not only of the regime but also of the actors that intervened in the process, leading to the configuration of political and school cultures that impacted not only teacher training, but also the institutions in charge of carrying it out. Which allowed structuring new paths that ended up reconfiguring educational policies and teacher cultures. In the case of Michoacán, although the process began in the Colony, it was not structured under systematic elements until the arrival of the Porfiriato and the establishment of the first attempts to create ex-professed teacher training institutions that took place around 1885. From that the process of preparation of the teaching profession went through conjunctures that represented the political intentions of the regional and national actors and that meant an important shift in the way in which not only education was understood, but also the role and duty of the teaching profession, this process allowed the existence of two teacher training policies in the state, one state and the other federal, both coexisting and developing, although not free of difficulties, which meant, around 1949, the suppression of the state policy and the federalization of the teacher training process with which most of the difficulties faced by Normal Education in the state tended to contract.

La formación de maestros en el país se ha configurado como un proceso de largo aliento que se vio influenciado por el contexto sociohistórico por el que atravesó, llegando a reconfigurarse, mutarse y transformase para adaptarse a las necesidades político-sociales no solo del Estado sino de la sociedad en su conjunto. El eje de transformación giró en torno a la intencionalidad política no solo del régimen sino de los actores que intervinieron en el proceso, llevando a configurar culturas políticas y escolares que impactaron no solo a la formación docente, sino también a las instituciones encargadas de llevarla a cabo, lo que permitió estructurar nuevos derroteros que terminaron por reconfigurar las políticas educativas y las culturas magisteriales. Para el caso de Michoacán si bien el proceso inició desde la Colonia no se estructuró bajo elementos sistemáticos sino hasta la llegada del porfiriato y el establecimiento de los primeros intentos por crear instituciones de formación docente exprofeso que acontecieron hacia 1885, a partir de ese momento la preparación del magisterio transitó por coyunturas que representaron las intenciones políticas de los actores regionales y nacionales y que significaron un viraje importante en la forma en que se entendía no solo la educación sino la función y el deber de la profesión magisterial, dicho proceso permitió la existencia de dos políticas de formación docente en el estado, una estatal y la otra federal, ambas conviviendo y desarrollándose, aunque no libres de dificultades, las cuales significaron hacia 1949 la supresión de la política estatal y la federalización del proceso de formación docente con lo que la mayoría de las dificultades que enfrento la Educación Normal en el estado tendieron a contraerse.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Doctorado en Historia
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16575; info:eu-repo/classification/cti/4; IIH-D-2023-1112; Historia de la educación; Educación normal; Políticas educativas